Respiratory tactics during cardiopulmonary bypass in cardiac surgery - A. Yu. Kirillov; A. G. Yavorovskiy; M. A. Vyzhigina; R. N. Komarov; P. V. Nogtev; P. S. Bagdasarov; E. Yu. Khalikova; D. A. Yavorovskaya; I. I. No (Вестник анестезиологии и реаниматологии)
An important place in the structure of the causes of postoperative respiratory failure in cardiac surgery is occupied by atelectasis of the lung tissue, which is formed during cardiopulmonary bypass (CPB). The incidence of this complication makes 54–92%.The objective: to evaluate the effectiveness of various respiratory support techniques during CPB.Subjects and methods. 60 patients were randomly included in the study. CPAP Group (positive airway pressure +5 cm H2O) and VC Group (lung ventilation during CPB with parameters: tidal volume 3 ml/kg, respiratory rate 6/min, positive end-expiratory pressure +5 cm H2O).Results. The oxygenation index in VC Group was higher than in CPAP Group at the stages after the end of CPB (289.6 ± 100.0 in VC Group and 223.1 ± 152.0 in CPAP Group), at the end of surgery (in VC Group 318,7 ± 73.8 and in CPAP Group 275.2 ± 90.0) The frequency of intraoperative (VC 16% and CPAP 43%) and postoperative recruiting lung maneuvers (VC 7% and CPAP 26%) in VC Group was lower versus CPAP Group. The incidence of atelectasis in VC Group (10%) decreased compared to CPAP (36.6%).Conclusion: Low-volume ventilation during cardiopulmonary bypass has a more favorable effect on the oxygenating function compared to respiratory support in the CPAP mode.